Influence of Female boardroom presence on firm value: An analysis on companies listed on B3. - Oliveira, Isaac Gezer Silva de; Cardoso, Sâmela Pedrada; Dias, Ricardo Santos; Júnior, Pedro Borges (Revista de Negócios, 2019)
In recent decades women have had substantial advances in access to higher education and the labor market, but these achievements were not reflected in the high ranking of companies. The participation of women in executive positions in the advisory board of large corporations in Brazil and in the world is still incipient. In this sense factors such as patriarchy, male chauvinism, sexism, among other advances not allow the presence of women at the top of large companies, even when this presence is associated with better performance. Thus, work on the assumption that thinking gender diversity of public policies involves ethical issues and inclusion strategies going performance improvement field and value creation, while the completion of ideas and attitudes from the specificities of each gender can contribute to economic and social development of the company. Thus the aim of this study is to investigate the relationship between corporate value and the presence of women in high-ranking. Therefore, we collected data of companies listed on the B3 and identified those with the presence of women on the board and the executive board, checking the differences between them from non-parametric tests. It is still employed multivariate data analysis from the linear regression and probit regression. The results suggest a positive and statistically significant relationship between firm value and the presence of women on the board. The results show evidence that the inclusion of women on the board in addition to ensuring diversity, meet precepts of ethics, equality, social responsibility, contributing to the better performance of firms and generating shareholder value.